The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0897190017752713
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Student Monitoring of Direct Oral Anticoagulants

Abstract: Pharmacy students can help to ensure medication safety and effective use of DOACs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…4 This study found that student pharmacists can help ensure medication safety and effective use of DOACs, however similar to the other studies, it did not assess the impact participation had on student pharmacists. 4 A study by Dunkley and colleagues also examined the utilization of student pharmacists to provide medication education on anticoagulants, inhalers, insulin, and naloxone. This study utilized 10 student pharmacists and found participants felt sufficiently to exceedingly prepared to perform medication education.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…4 This study found that student pharmacists can help ensure medication safety and effective use of DOACs, however similar to the other studies, it did not assess the impact participation had on student pharmacists. 4 A study by Dunkley and colleagues also examined the utilization of student pharmacists to provide medication education on anticoagulants, inhalers, insulin, and naloxone. This study utilized 10 student pharmacists and found participants felt sufficiently to exceedingly prepared to perform medication education.…”
mentioning
confidence: 71%
“…2 While several studies have examined pharmacy student involvement in patient counseling services, the impact of participation in patient education on student knowledge and perceptions remains underexplored. [2][3][4][5][6] The majority of studies available concerning pharmacist and pharmacy student involvement in inpatient anticoagulation education focus on warfarin with less emphasis on direct oral anticoagulants (DOACs). Wilhelm and colleagues specifically looked at the impact of an anticoagulation service using pharmacy students and residents on rate of education completed and effect of providing education on overall and anticoagulation-associated readmission rates.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In an observational analysis conducted in an internal medicine clinic, a pharmacy student program designed to monitor direct oral anticoagulants demonstrated that the most common intervention was related to medication adherence. 20 Therefore, future research may consider expanding clinical services involving pharmacy students to other high-risk medication classes that suffer from low adherence rates. Given that we only investigated statins in this study as a pilot project, future studies investigating adherence to other medications included in the CMS star measures (renin-angiotensin system antagonists or oral antidiabetic agents) are needed.…”
Section: Baseline Characteristics For Statin Users (N = 99)mentioning
confidence: 99%